Application of Computational Fluid Dynamics to flow next to high-rise buildings in Hong Kong due to air-conditioner heat rejection. (5th February 2008) - Bojic, M.; Savic, S.; Nikolic, D.
This paper presents the results of several studies done for high-rise residential buildings in Hong Kong that involved Computational Fluid Dynamics (CFD) simulation. During summer, a number of Window Air-Conditioners (WACs) could be rejecting condenser heat into a recessed space of these high-rise residential buildings. FLUENT 5.0, a CFD code can be used to predict temperatures and flow field of a powerful rising hot air stream formed in the recessed space. In these cases, for simulations, we use κ-ε turbulence model, and 2D and 3D model of the building. A CFD code can also be used to predict temperature and flow fields inside the recessed spaces that differ in heights and condenser-unit locations. The CFD code also employed to predict the airflow patterns. The papers study the worst-case scenario in summer when all the WAC units reject condenser heat into this space.